Intrahepatic cholestasis of pregnancy: maternal and fetal outcome and its correlation with serum bile acid levels - Sharma, Bhawna; Arora, Neetu; Dogra, Kusum; Negi, Kamal S. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Maternal, fetal, and neonatal outcomes in parturients with intrahepatic cholestasis of pregnancy (ICP) have been retrospectively documented. We aimed to present pregnancy outcomes of parturients with ICP who underwent delivery. The study was conducted during a 1-year period in a tertiary care centre. Methods: Data from 1 January to 31 December 2017 were collected to identify parturients with ICP. Results: Almost 3/4th of births came to a vaginal delivery (76.74%) and only 10 parturients had cesarean delivery. 4 of 10 parturients underwent nonelective cesarean section, while 6 had elective cesarean delivery. 15.15 % vaginal deliveries were instrumental. The most common indications for emergency LSCS and instrumental deliveries was fetal distress followed by failure to progress of labour. Most births occurred at or after 37 weeks of gestation (65%). Regarding neonatal outcomes in terms of birth weight and Apgar scores at 1 and 5 min, they were positive, as well. None of the babies had Apgar score < 7 at 5 minutes. No case of perinatal death was observed. Conclusions: Although the results were generally positive, larger studies need to be conducted to evaluate the maternal and fetal outcomes in ICP and correlation with serum bile acid levels.